39.0k views
3 votes
I need some help with math

User Zeh
by
5.2k points

1 Answer

3 votes

3x^2-14x=-15

start by bringing all terms to the left of the equation


3x^2-14x+15=0

multiply the equation by the leading coefficient


9x^2-42x+45=0

use a substitution u=3x, because it is the square root of the first term,


u^2-14u+45=0

factor using the solutions -9 and -5 since multiplied together they give a result of 45 and added together -14


(u-9)(u-5)

replace with the substitution used


(3x-9)(3x-5)

then, divide by the 3 we multiplied in the first step


(x-3)(3x-5)

Answer:


(x-3)(3x-5)
\begin{gathered} 3x^2-5x-9x+15 \\ 3x^2-14x+15 \end{gathered}

User Dulce
by
5.1k points